2007
DOI: 10.1080/15252019.2007.10722136
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effects of Incidental Advertising Exposure in Online Gaming Environment

Abstract: This study addresses incidental advertising exposure effects in online games by manipulating both the location (low proximity versus high proximity) and the message content (visual versus verbal) of an incidental cue while participants' primary attention is diverted by playing an online game. The results reveal that incidental exposure can be effective if the secondary stimulus appears very close to the focal attention area. The study also finds no incidental effects of text inside bars or images in address ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 49 publications
2
34
0
1
Order By: Relevance
“…They may play the scenarios repeatedly and be exposed to the in-game advertisements for a prolonged period of time. Repeated exposure breeds familiarity or perceptual fluency which makes it easier for the gamers to process the advertisement and hence recall the advertised brands to a larger extent (Acar, 2007;Leng et al, 2010;Schneider & Cornwell, 2005). It is this argument that has yet to be tested that lays the promise of in-game advertisements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may play the scenarios repeatedly and be exposed to the in-game advertisements for a prolonged period of time. Repeated exposure breeds familiarity or perceptual fluency which makes it easier for the gamers to process the advertisement and hence recall the advertised brands to a larger extent (Acar, 2007;Leng et al, 2010;Schneider & Cornwell, 2005). It is this argument that has yet to be tested that lays the promise of in-game advertisements.…”
Section: Discussionmentioning
confidence: 99%
“…Advertisements that appear in situations or locations that are central to the game are recalled at a higher rate than those that are peripheral to the game (Acar, 2007;Chaney, Lin, & Chaney, 2004;Lee & Faber, 2007;Leng, Quah, & Zainuddin, 2010;Schneider & Cornwell, 2005). For example, in sports racing games, advertisements that appear near the car are more likely to be remembered than advertisements which are further removed from the car.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For example, empirical studies reveal that brand alliances and co-branding strategies can be a viable means of transferring attitudes from a brand to a website and vice versa (Delgado-Ballester & Hern谩 ndez-Espallardo, 2008). Furthermore, brand placement in digital games and virtual worlds has been proven to enhance brand image (Molesworth, 2006) and even incidental exposure to brands during games influences consumer decisions (Acar, 2007). Based on these lines of reasoning, we assume that operating or sponsoring a virtual community positively affects attitudes towards the operating or sponsoring brand.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…22 The relationship between the level of involvement in the game and the rate of recall and recognition of in-game advertisements, however, are more complex. Lang 23 suggested that people are information processors.…”
Section: Gamers Are Also Consumersmentioning
confidence: 99%